1975
DOI: 10.1210/endo-97-4-771
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Estrogen-Progesterone Combinations on Gonadotropin Secretion in Castrate Female Rats1

Abstract: In order to study the effect of progesterone in modulating the secretion of gonadotropins, various doses of progesterone were administered to castrated immature and mature female rats. Progesterone did not prevent the postcastration rise of FSH and LH in these animals. Various amounts of progesterone were then administered to castrated rats that were treated with a constant low dose of estradiol. In animals given doses of estradiol that were able to decrease serum FSH and LH below castrate levels, but not to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(20 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…P did not suppress pulse frequency when replaced for 24 h either at the time of OVX on Dl [27] or 1 week later (present report). These re sults agree with other reports which have indicated that physiological or pharmacological levels of P decreased LH secretion in acute but not long-term ovariectomized rats [6,7,12,19,20,33,35,43]. Recently, Weick and Noli [44] re ported in long-term ovariectomized rats that P alone had either no effect on any parameter of pulsatile LH secretion or.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…P did not suppress pulse frequency when replaced for 24 h either at the time of OVX on Dl [27] or 1 week later (present report). These re sults agree with other reports which have indicated that physiological or pharmacological levels of P decreased LH secretion in acute but not long-term ovariectomized rats [6,7,12,19,20,33,35,43]. Recently, Weick and Noli [44] re ported in long-term ovariectomized rats that P alone had either no effect on any parameter of pulsatile LH secretion or.…”
Section: Discussionsupporting
confidence: 91%
“…This effect occurred whether these steroids were replaced for 24 h I week following OVX (present report) or at the time of OVX [27]. The greater suppression of LH secretion by the com bined action of E2 and P agrees with other reports which clearly indicated that these steroid hormones act together to suppress LH release in ovariectomized rats [6,19,20,33,35,43,44]. Since pulses of LH are due to pulses of LHRH [I I, 29], the suppressive effects of E2 + P on LH pulse fre quency are presumably due to decreasing the frequency of LHRH release.…”
Section: Discussionsupporting
confidence: 90%
“…The effects of steroids on gonadotropin secretion in which one set of doses are stimulatory while others are inhibitory are well documented in the literature, particularly with respect to progesterone (7,18,19). More recently we have demonstrated the same effect with dexamethasone (20).…”
Section: Discussionsupporting
confidence: 66%
“…(11) and prolactin release (12) were not impaired. In view of our previous work revealing the 0.2 mg/kg body wt and 0.8 mg/kg body wt doses of progesterone were effective in inducing luteinizing hormone and follicle-stimulating hormone surge in low dose estrogen-primed ovariectomized immature rats while the intermediate dose of 0.4 mg/kg body wt was ineffective (18), the effect of different doses of progesterone on occupied nuclear estradiol receptors of the anterior pituitary was investigated by Fuentes et al (13). The work of Fuentes et al (13) in the adult rat showed that the 0.8 mg/kg body wt and 4.0 mg/kg body wt doses of progesterone were more effective in reducing occupied pituitary estrogen receptor binding (60% and 71% reduction) as compared to the 2mg/kg body wt dose (33% reduction).…”
Section: Discussionmentioning
confidence: 81%
“…Le et al 1997, Yen & Pan 1998. Simultaneous treatment with both estrogen and progesterone appears to suppress the steroid-induced LH surge (Legan et al 1973, McPherson et al 1975, Attardi 1981. One limitation of administering steroids by implanting pellets is that constant high levels of estrogen and/or progesterone desensitize the pituitary gland to subsequent estrogen or GnRH stimulation (for review see Gharib et al 1990).…”
Section: Introductionmentioning
confidence: 99%